2013
DOI: 10.1002/erv.2247
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Eating Disorders and Their Relationship to Clinical Profile

Abstract: In this study, patients with AN showed an impairment in affective ToM, independent of their clinical status. Consistent with other studies, our findings demonstrate a specific difficulty in social cognition in patients with AN. This may be a trait marker in this population and should be considered in treatment. Furthermore, patients with AN and BN have different difficulty profiles in this domain of social cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
3
21
1
1
Order By: Relevance
“…Two functional MRI studies that used a behavioral task in the scanner to assess neural response toToM task were not included as they were not designed to detect subtle deficits in social cognition . Having an unspecified type of EDNOS (1 sample from Medina‐Pradas et al), the inclusion of male patients, being reported as a conference abstract (1 study) and being based on an overlapping sample with an included study were other reasons for exclusion from the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two functional MRI studies that used a behavioral task in the scanner to assess neural response toToM task were not included as they were not designed to detect subtle deficits in social cognition . Having an unspecified type of EDNOS (1 sample from Medina‐Pradas et al), the inclusion of male patients, being reported as a conference abstract (1 study) and being based on an overlapping sample with an included study were other reasons for exclusion from the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Two functional MRI studies that used a behavioral task in the scanner to assess neural response toToM task were not included as they were not designed to detect subtle deficits in social cognition. 36,37 Having an unspecified type of EDNOS (1 sample from Medina-Pradas et al 31 ), the inclusion of male patients, 38 being reported as a conference abstract (1 study) and being based on an overlapping sample with an included study 39,40 were other reasons for exclusion from the meta-analysis. 22 ED samples (reported in 15 published studies) involving 677 (all females) individuals with eating disorders and 514 (females) healthy controls were included 6,[24][25][26][27][28][29][41][42][43][44][45][46][47] (Table 1) (see the Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The Eyes Test is a brief online test where participants are shown photographs of the eye regions and have to identify the appropriate emotion or mental state they express2. It has been widely used to investigate differences in cognitive empathy in a range of neuropsychiatric conditions including autism4, schizophrenia9, bipolar disorder10, anorexia nervosa11, and major depressive disorder12. The NIMH Research Domain Criteria (RDoC) lists the Eyes Test as one of several important tests for characterizing variation in social processes, under the category of Perception and Understanding of Others (http://1.usa.gov/1Qs6MdI)13.…”
Section: Introductionmentioning
confidence: 99%
“…Theory of mind has been evaluated in eating disorders such as anorexia nervosa and bulimia. Several studies have reported impaired theory of mind in anorexic patients (Russell, Schmidt, Doherty, Young, & Tchanturia, ; Tapajóz Pereira de Sampaio, Soneira, Aulicino, & Allegri, ), whereas it seems to be preserved in patients with bulimia (DeJong et al, ; Tapajóz Pereira de Sampaio et al, ). Following a procedure similar to ours, a recent study has reported difficulties in children and adolescents with obesity in understanding others' mental states from eye gaze (Percinel, Ozbaran, Kose, Simsek, & Darcan, ), but data from adult population with obesity are lacking.…”
Section: Introduction and Aimsmentioning
confidence: 99%